Analysis of Critical Factors Influencing Project Performance in Construction Projects at CV Adhi Citra Haryo Seto - Seto, Adhimas Kunto Haryo; Anwar, Muhadjir; Waluyo, Minto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Construction projects often face challenges in meeting cost, time, and quality targets. This study aims to analyze: the effect of top management support as a critical factor on project performance, the effect of project team competence as a critical factor on project performance, the effect of green project practices as a critical factor on project performance, and the mediating role of project management effectiveness in these relationships. The research was conducted at CV Adhi Citra Haryo Seto, which managed seven projects during 2023–2025, involving 103 project personnel as respondents. Data were collected using questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4. The findings indicate that project performance at CV Adhi Citra Haryo Seto improves when top management provides consistent support, project teams demonstrate adequate competencies, and green project practices are effectively implemented. These three factors are reinforced through project management effectiveness, where well-prepared planning, structured coordination, and responsive control serve as the bridge that translates leadership support, team capabilities, and green project practices into tangible achievements in cost, time, quality, and project sustainability.